Moralitas Haya sebagai Core Value Pendidikan Karakter - Isti’anah Abubakar (Fak. Tarbiyah UIN Maliki Malang, 2012)
One of the seven fatal sins of education without character is the expression of Mahatma Gandhi on the importance of character education. This is because (1) the world is changing, (2) increasing the attidute of selfishness an a violence of the rights of people to commit violence against others, (3) the attitude of students has changed. Historically , the current character education is a complement of education formula itself has not been effective. For the core value that needs to be explored is used as the formula of the formation of character values , announced the Ministry of Educational Education. Haya can be used as core values because may hadits that reveal the definition, process and impact. This discussion is a discussion paradigmatik remains controversial give the meaning of haya.